Improving Performance on Low-Level Audit Tasks: The Interactive Effect of Regulatory Fit and Professional Identity - Mendoza, Kim I.; Winn, Amanda (The Accounting Review, 2022)
ABSTRACT Auditing standards vary in their degree of prescriptive language—for example, stating that auditors “could” versus “should” do certain procedures. We posit that more prescriptive language primes an implemental mindset, thereby creating a feeling of regulatory fit with objective verification tasks and improving auditors' performance on these tasks. In an experiment with audit students, we find that participants who apply a more (versus less) prescriptive auditing standard perform better on a subsequent, unrelated ticking-and-tying task, and this effect is larger for participants who identify less with the audit profession. Theory-consistent evidence indicates that the interaction of regulatory fit and professional identity improves performance via increased motivation. Our study provides evidence that features of the audit environment prime mindsets, that these primed mindsets can affect performance on low-level tasks, and that the effect of regulatory fit for low-level tasks is particularly important for those who identify less with the audit profession.